Recent Progress on the Performance of Different Rate Promoters in Potassium Carbonate Solvents for CO2 Capture. (July 2017) - Hu, Guoping; Smith, Kathryn; Wu, Yue; Kentish, Sandra; Stevens, Geoff
Abstract: Over recent years our research group has examined the performance of a range of rate promoters in potassium carbonate solvent for carbon dioxide absorption. Promoters including boric acid, potassium glycinate, potassium prolinate, potassium sarcosinate and a thermally stable carbonic anhydrase enzyme have been studied either with the stopped flow technique, a wetted wall column or in the pilot plant located at The University of Melbourne in Australia. The carbonic anhydrase enzyme was shown to have the best promotion performance. However, improvements are required in further improving thermal stability and recycling options in order for the enzyme to be applied in industrial solvent absorption processes. Amino acid salts including potassium sarcosinate, prolinate and glycinate were proven to have high promotion performance at bench scale. Pilot plant results showed that the promotion performance of boric acid was poor, while potassium glycinate was a good rate promoter with an increase in absorption rate of up to 5–6 times when adding 10 wt. % glycinate into 40–45 wt. % potassium carbonate solvent.